Hybrid DE and PEM algorithm for identification of small scale Autonomous helicopter model - Legowo, Ari (s.n, 2012)
A hybrid identification algorithm based on Differential Evolution (DE) and PEM is proposed in this study for effective identification of a small scale helicopter's model parameters. The proposed hybrid identification method explored the evolutionary search optimization strength of DE for parameter initialization for PEM identification algorithm